2022
DOI: 10.3390/ijms23031490
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Death in Myeloproliferative Neoplasms: Shedding More Light on Neutrophils as a Pathogenic Link to Chronic Inflammation

Abstract: Neutrophils are an essential component of the innate immune response, but their prolonged activation can lead to chronic inflammation. Consequently, neutrophil homeostasis is tightly regulated through balance between granulopoiesis and clearance of dying cells. The bone marrow is both a site of neutrophil production and the place they return to and die. Myeloproliferative neoplasms (MPN) are clonal hematopoietic disorders characterized by the mutations in three types of molecular markers, with emphasis on Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 188 publications
0
8
0
Order By: Relevance
“…These findings are in line with previous in vitro reports showing that palmitic acid was involved in mediating apoptosis and pro-inflammatory response in immune cells, which were effects not observed with oleic acid, EPA or DHA ( Hidalgo et al, 2021 , Radzikowska et al, 2019 ). It is known that the sterile inflammation in the bone marrow microenvironment can converge in the activation of granulocytes ( Markovic, Maslovaric, Djikic, & Cokic, 2022 ) and that the feeding of a lard-enriched HFD for only 1 week to wild-type C57BL/6J mice can enhance differentiation of myeloid progenitors into neutrophils ( Huang et al, 2017 ). Therefore, our data support the notion that the occurrence of early apoptotic events in bone marrow neutrophils during the early-phase of obesity can be compensated with increased production, activation and mobilisation of new neutrophils from the own bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous in vitro reports showing that palmitic acid was involved in mediating apoptosis and pro-inflammatory response in immune cells, which were effects not observed with oleic acid, EPA or DHA ( Hidalgo et al, 2021 , Radzikowska et al, 2019 ). It is known that the sterile inflammation in the bone marrow microenvironment can converge in the activation of granulocytes ( Markovic, Maslovaric, Djikic, & Cokic, 2022 ) and that the feeding of a lard-enriched HFD for only 1 week to wild-type C57BL/6J mice can enhance differentiation of myeloid progenitors into neutrophils ( Huang et al, 2017 ). Therefore, our data support the notion that the occurrence of early apoptotic events in bone marrow neutrophils during the early-phase of obesity can be compensated with increased production, activation and mobilisation of new neutrophils from the own bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been described that the MPN BM stem cell niche is a place of chronic inflammation characterized by raised myeloproliferation, altered neutrophil apoptosis, and, probably, unbalanced neutrophil marginal and reserve pool. The specific alterations of these compartments are induced by the inflammatory stimuli and, in turn, can have a major impact on the resolution of inflammation in the MPN, both in the BM and in the peripheral blood, thus influencing the pathogenesis and progression of the disease [ 27 ]. Noteworthy, it has been reported that the JAK2 mutation, at the center of the MPN pathogenesis, activates the STAT3 signaling pathway, which is involved in a variety of inflammatory cytokines expressions causing inflammation and dysfunction of the immune system [ 28 ].…”
Section: Bone Marrow Microenvironmentmentioning
confidence: 99%
“…In MPNs, even though it seems obvious for secondary necrosis or other forms of lytic neutrophil death to intervene in disease progression by supporting inflammation, no reliable data are available, and when relying on NET studies, one encounters NET data that are predominantly presented in the context of thrombosis as a MPN-associated complication, rather than in the context of lytic NETotic death or vital NET formation and their impact on inflammation and fibrosis in MPN pathology [99][100][101][102][103]. In our recently published paper, we argued that neutrophil death in MPNs is mirrored by defects in apoptosis and listed a set of postulates that could act in support of the statement that the apoptosis of neutrophils supervises the duration and intensity of an inflammatory response, as well as the extent of neutrophil-mediated tissue damage [36]. The findings that MPN neutrophils are primed for NET formation [100,101] and that the signaling pathways and regulatory molecules such as the JAK, STAT, AKT and Raf-MEK-ERK signal transduction pathway-which may regulate both apoptosis and NETs in normal neutrophils or neutrophils under pathological conditions [100,[103][104][105][106]-are upregulated in MPNs [5,12,[14][15][16][17][18]34] encouraged us to discuss the potential pathophysiological relevance of NET formation in MPNs in this review.…”
Section: Introductionmentioning
confidence: 95%
“…Different cellular sources in MPNs, in vivo, such as activated leukocytes, platelets, megakaryocytes, and bone marrow stromal cells, which constitute the bone marrow microenvironment or hematopoietic niche, continually release diverse inflammatory mediators, including inflammatory cytokines, chemokines, reactive oxygen species (ROS) and reactive nitrogen species (RNS) [16,29,33,34]. However, mutated (clonal) hematopoietic progenitors and mature blood elements, such as platelets and neutrophils, have been implicated in MPN development as key players underpinning MPN inflammation [21,22,26,32,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation